2004
DOI: 10.1002/jobm.200410384
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Citrobacter sp. mutants defective in decolorizing malachite green

Abstract: To identify genes involved in the decolorization of malachite green, random mutants generated by transposon insertion in the malachite green-decolorizing bacterium, Citrobacter sp. were isolated. The resulting mutant bank yielded 24 mutants with complete defects in their abilities to decolorize malachite green. Southern hybridization with a Tn5 fragment as a probe showed a single hybridized band in 7 mutants, which appeared to have insertions at different sites of the chromosome. The Tn5-inserted genes were is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In intestinal bacteria, HPLC analysis of Clostridium perfringens and Lactobacillus acidophilus cultures incubated with malachite green showed that malachite green was converted to leucomalachite green after 48 h (Henderson et al, 1997). In addition, Jang et al (2004) isolated Citrobacter strain KCTC 18061P, which is also very efficient in decolorization of malachite green. The enzyme triphenylmethane reductase, which catalyses the conversion of malachite green to colourless leucomalachite green, was purified and the gene cloned for heterologous expression in Escherichia coli.…”
Section: Introductionmentioning
confidence: 99%
“…In intestinal bacteria, HPLC analysis of Clostridium perfringens and Lactobacillus acidophilus cultures incubated with malachite green showed that malachite green was converted to leucomalachite green after 48 h (Henderson et al, 1997). In addition, Jang et al (2004) isolated Citrobacter strain KCTC 18061P, which is also very efficient in decolorization of malachite green. The enzyme triphenylmethane reductase, which catalyses the conversion of malachite green to colourless leucomalachite green, was purified and the gene cloned for heterologous expression in Escherichia coli.…”
Section: Introductionmentioning
confidence: 99%
“…KCTC 18061P, Pseudomonas sp. MDB-1, and Lactobacillus acidophilus cultures incubated with triphenylmethane dyes showed that these dyes were converted to leuco derivatives (Henderson et al 1997;Ren et al 2006;Jang et al 2004;Li et al 2009). These leuco derivatives, also as contaminants, were equally toxic to triphenylmethane dyes and were eliminated much slower than dyes from environment (Burchmore and Wilkinson 1993).…”
Section: Introductionmentioning
confidence: 96%
“…Several species of fungi are known to decolorize triphenylmethane dyes by a variety of enzymes as laccase (Casas et al 2009;Vasdev et al 1995), peroxidase (Shin and Kim 1998), lignin peroxidase (Bumpus and Brock 1988) or cytochrome P450 monooxygenase (Cha et al 2001) and the structural genes encoding laccase and lignin peroxidase have been cloned and characterized (Cullen 1997;Gold and Alic 1993). In recent years different bacteria capable of triphenylmethane dyes decolorization have been reported (Ayed et al 2009;Henderson et al 1997;Cheriaa and Bakhrouf 2009;Jang et al 2004;Jones and Falkinham III 2003;Li et al 2009;Ren et al 2006). Analysis of Clostridium perfringens, Aeromonas hydrophila DN322, Citrobacter sp.…”
Section: Introductionmentioning
confidence: 97%
“…Studies on the biodegradation of MG have focused primarily on decolorization via reduction reactions (2,14,16,17,20). In recent years, different bacteria capable of the decolorization of MG have been reported (7,8,10,13,19). Cultures of Clostridium perfringens, Aeromonas hydrophila DN322, Citrobacter sp.…”
mentioning
confidence: 99%
“…KCTC 18061P, Pseudomonas sp. MDB-1, and Lactobacillus acidophilus have been shown to convert MG to leucomalachite green (LMG) (7,8,13,19), which is less toxic to both mammalian and bacterial cells due to its insolubility in water (1). The biochemical mechanism underlying the decolorization has been elucidated in some bacteria.…”
mentioning
confidence: 99%